V Focus Sky Solution / Wesley Chong kah Ong and Voon Choon Teck - Ong, Wesley Chong kah; Teck, Voon Choon (2020)
Are you looking for educational materials? V Focus Sky Solution's PDPC is compatible with 21st century education. It provides latest syllabus such as KSSR, KSSM and MPEI. It contains all subjects inside. V Focus Sky Solution applies beautiful design, pictures, attractive videos and understandable I-Think Map to attach students' attention. As we are fighting against the COVID-19 outbreak, all the schools have been closed. To support Movement Control Order (MCO) during this critical period, V Focus Sky Solution had been providing free online education for both teachers and students during MCO period. As the time change, V Focus Sky Solution has come out an online version, especially for students. The Login Page is just like Facebook. After login, you can choose the subject and topic you want. From here, students can review back what they have learnt in the school anytime, anywhere. The Ministry of Education is now vigorously encouraging the use of Google Classroom for online education. Teacher can prepare the slides of V Focus Sky Solution in the Classwork and schedule the date to post, where the students also have the benefit to access the slide as well. There will be some questions and assessment which can be assigned to the students. By this way, teacher can monitor the progress of students, and consequently, will lead to more participation and interaction between teachers and students in Google Classroom.